Shri Dhirubhai Ambani receives 'Man of the Century' award - Reliance Industries Limited (2022)
The Chemtech Foundation and Chemical Engineering World, India's leading industry association, conferred on Shri Dhirubhai Ambani the ‘Man of the Century' award in recognition of his outstanding contribution to the growth and development of the chemical industry in India.